DIFFERENTIATED APPROACH TO THE SURGICAL EXTRACTION OF WISDOM TEETH - A.I. Pankevych; I.A. Kolisnyk; A.M. Hohol (Ukrainian Medical Stomatological Academy, 2019)
Impaction and malposition of wisdom teeth and associated inflammatory and tumor-like complications occur in 35-50% of the able-bodied population. The operation of surgical extraction of the third molar of the mandible is indicated for these patients and this operation is one of the most common in surgical dentistry today.Alsoasignificant indication for wisdom teeth removaliscrowding of teeth. The classic operation of surgical wisdom tooth removal, even with careful planning, can be accompanied by different intraoperative and postoperative complications. Planning of removal of the third lower molar requires an individual approachwith mandatory consideration not only of the tooth position but also the topography of the causative tooth relative to the adjacent tooth and mandibular canal. Among the surgical procedures which are used to remove wisdom teeth, in addition to the classic surgery extraction, coronectomy and germectomy should be noted. The purpose of our study was to analyze the advantages and disadvantages of different techniques used for surgical extraction of impacted and malposition wisdom teeth. 208 operations regarding the removal of the third lower molars have been performedduring 2016-2019, of which surgical wisdom teeth removal were 213, coronectomies - 23 and germectomies - 29.Patients' ages ranged from 13 to 26 years. A germectomy was performed in 13-16 years old patient, usually at the stage of a fully formed tooth crown or at the beginning of root formation. The choice of surgery in patients with fully formed roots was dependent on the ratio of the root of the tooth and mandibular canal, which was evaluated after a preliminary computer examination, taking into account the complexity of the surgery and the prognosis of complications. Acoronectomy operation was performed with the close location of the roots of the wisdom tooth with the mandibular canal, taking into account the risk of the damage of lower alveolar nerve. Germectomy and surgery of wisdom teeth removal were performed according to the classical method with cutting of mucoperiostal flaps, preparation of bone, if necessary - separation of crown and roots with subsequent removal of the germ or tooth. The crown of wisdom tooth was separated with a coronectomy, (and cut in height with insufficient access) and the tooth crown was removed, leaving the roots in the jaw. Patients were observed on the next day after surgery, a week later, and as needed. The course of the postoperative period was evaluated: the presence of pain, swelling, complications. The duration of follow-up was up to 2 years. Conclusions: To the choice of surgery in patients with impaction and malposition of wisdom teeth should be approached in a differentiated manner, taking into account topographic and anatomical features, including the ratio of the roots of the teeth to the mandibular canal and assessing the risks of possible complications. Germectomy and coronectomy surgery can be recommended as surgery of choice for orthodontic indications in the treatment of patients with crowded teeth.